Tentang Upaya Pencegahan Penularan Tuberculosis Paru Hubungan Tingkat Pengetahuan dengan Sikap Masyarakat - Yuni Anjelina; Fitriani Ningsih; Riska Ovany (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Tuberculosis is still a global public health problem that is a worldwide challenge. One of the causes of the lack of general knowledge in efforts to prevent the transmission of Tuberculosis is the lack of information and education from health workers or posyandu cadres about Tuberculosis, resulting in a lack of public knowledge about Tuberculosis. This study aims to explain